2017
DOI: 10.1002/cctc.201700305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acid–Base Properties and the Activity of ZrO2‐Based Catalysts for the Cannizzaro Reaction of Pyruvaldehyde to Lactic Acid

Abstract: The Cannizzaro reaction of pyruvaldehyde to lactic acid is investigated in a flow reactor with ZrO2 catalysts with different structures and acid–base properties. The results show that a difference in the crystalline structures of two ZrO2 polymorphs strongly affects the conversion of pyruvaldehyde. The monoclinic phase of zirconia is the most active for this reaction. A good correlation is observed between the reaction rate and the concentration of Lewis acid sites of sufficient strength, which shows that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…The significant production of formaldehyde over the catalysts with no or low concentration of water‐tolerant acid sites, SnO 2 and ZrO 2 , demands some attention as well. Formaldehyde has not been observed as a product in pyruvaldehyde conversion at this reaction temperature, and thus, the reaction pathway leading to it could start as a sequential reaction from lactic acid or as a parallel reaction path for glyceraldehyde conversion. No conversion was observed at all over these two catalysts when lactic acid was used as starting material under the same reaction conditions (130 °C, 10 bar, flow of 0.3 mL min −1 and W/F=1 g min mL −1 ) in a control experiment (Figure S3).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The significant production of formaldehyde over the catalysts with no or low concentration of water‐tolerant acid sites, SnO 2 and ZrO 2 , demands some attention as well. Formaldehyde has not been observed as a product in pyruvaldehyde conversion at this reaction temperature, and thus, the reaction pathway leading to it could start as a sequential reaction from lactic acid or as a parallel reaction path for glyceraldehyde conversion. No conversion was observed at all over these two catalysts when lactic acid was used as starting material under the same reaction conditions (130 °C, 10 bar, flow of 0.3 mL min −1 and W/F=1 g min mL −1 ) in a control experiment (Figure S3).…”
Section: Discussionmentioning
confidence: 88%
“…The concomitant drop in pyruvaldehyde selectivity evidences that the Cannizzaro reaction in the end of the cascade reaction path is accelerated. Albuquerque et al . have indeed shown that pyruvaldehyde rearrangement to lactic acid is improved at high temperature.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations